Lugol chromoendoscopic screening for esophageal dysplasia/early squamous cell carcinoma in patients with esophageal symptoms in low-risk region in China - SHAO, YING (Oncol Lett, 2015)
Detection of esophageal dysplasia/early esophageal squamous cell carcinoma (ESCC) is essential for improving 5-year survival. The aim of this prospective study was to evaluate whether Lugol chromoendoscopy improves the detection of esophageal dysplasia/early ESCC in patients with esophageal symptoms in a low-incidence region in China. Eligible patients were randomly assigned into two groups who received routine endoscopy or Lugol chromoendoscopy. During endoscopy, between one and five biopsies were taken from visible lesions for routine endoscopy, or unstained areas of >0.5 cm in diameter for Lugol chromoendoscopy. In total, 812 patients were enrolled, 395 for routine endoscopy and 417 for Lugol chromoendoscopy. The overall detection rate of esophageal dysplasia/early ESCC was 10.6% (86/812), the detection rates were 7.3% (29/395) and 13.7% (57/417) in routine and chromoendoscopy groups, respectively (χ(2)=8.58, P=0.003). The detection rates were 8.3% (48/580), 17.2% (17/99) and 16.5% (22/133), respectively, in patients with reflux, dysphagia and globus sensation symptoms. In the chromoendoscopy group, 213 patients had unstained lesions of >0.5 cm, the detection rates of dysplasia/early carcinoma were 5.3% (4/76) in those with lesions of 0.5–1.0 cm, and 37.2% (51/137) in those with lesions >1.0 cm (χ(2)=21.46, P<0.001). These results indicate that Lugol chromoendoscopy improves the detection rate of esophageal dysplasia/early carcinoma in patients with esophageal symptoms compared with routine endoscopy. We propose that Lugol chromoendoscopy must therefore be considered in addition to routine endoscopy in patients with esophageal symptoms.